2004
DOI: 10.1161/01.cir.0000121427.53291.78
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone-Marrow Mononuclear Cell Implantation Improves Endothelium-Dependent Vasodilation in Patients With Limb Ischemia

Abstract: Background-Patients with limb ischemia were associated with endothelial dysfunction. The purpose of this study was to determine whether autologous bone-marrow mononuclear cell (BM-MNC) implantation improves endothelial dysfunction in patients with limb ischemia. Methods and Results-We evaluated the leg blood flow (LBF) response to acetylcholine (ACh), an endotheliumdependent vasodilator, and sodium nitroprusside (SNP), an endothelium-independent vasodilator, before and after BM-MNC implantation in 7 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
0
14

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(186 citation statements)
references
References 18 publications
9
163
0
14
Order By: Relevance
“…These results remained stable until the 24-week follow-up. Two other studies, using a similar approach in seven and eight patients with CLI, confirmed the safety and feasibility of intramuscular BM-MNC transplantation in PAOD (128,129). Moreover, Higashi et al assessed an improvement in endothelium-dependent vasodilatation after BM-MNC implantation in these patients with limb ischemia.…”
Section: Peripheral Arterial Occlusive Diseasementioning
confidence: 78%
“…These results remained stable until the 24-week follow-up. Two other studies, using a similar approach in seven and eight patients with CLI, confirmed the safety and feasibility of intramuscular BM-MNC transplantation in PAOD (128,129). Moreover, Higashi et al assessed an improvement in endothelium-dependent vasodilatation after BM-MNC implantation in these patients with limb ischemia.…”
Section: Peripheral Arterial Occlusive Diseasementioning
confidence: 78%
“…21 Although BMMNC or M-PBMNC intramuscular implantation has been used most often, both therapies have some risk: to collect about 500 mL of BMMNC, general anesthesia of about 4 h duration is necessary, and to collect PBMNC, about 3 h of apheresis with G-CSF treatment is required. [2][3][4][5][6][7][8][9][10][11][14][15][16][17][18] In a first cell-therapy trial, results of which were published in 2002, 22 ASO patients (44 limbs) were implanted with either BMMNC or PBMNC. 2 At 6 months after implantation, both therapies yielded improvements in terms of rest pain, ABI and transcutaneous oxygen pressure, but the clinical outcomes for BMMNC were significantly better than those for PBMNC.…”
Section: Introductionmentioning
confidence: 99%
“…Outra possibilidade é a de que as próprias CTA produziriam esses fatores de estímulo, que concorreriam para a formação de novos vasos, inclusive estimulando CP "residentes" na região isquêmica (atividade paracrina) [40][41][42] , e ainda concorreriam para a melhora do funcionamento do endotélio dos vasos remanescentes, além de promover a sua vasodilação 43 . É provável que haja uma associação desses vários mecanismos para que haja vasculogênese.…”
Section: Células Endoteliais Progenitorasunclassified
“…Higashi et al 43 demonstraram que o implante de células mononucleares de medula óssea melhorava a vasodilatação dependente do endotélio em pacientes com isquemia de membros inferiores, isto é, melhorava o desempenho do endotélio dos vasos remanescentes.…”
Section: Experiências Clínicas Com Células-tronco Adultasunclassified